2012
DOI: 10.1111/j.1440-1584.2012.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional paediatric poisoning in rural Victoria: Incidence and admission rates

Abstract: Although rates of paediatric poisoning seem to be lower in this particular rural setting, admission rates continue to be significantly higher than comparative urban figures. Further research and education is needed to gain a better understanding of this important public health topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…All cases under the age of 6 years were due to accidental poisoning. This is consistent with both developed and developing countries that younger children are over- represented in acute accidental poisoning [ 3 , 5 , 11 ]. This is due to younger children being more inquisitive and exploratory in nature compounded by their newly acquired hand skills and mobility and increased the tendency to mouth objects [ 15 , 30 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…All cases under the age of 6 years were due to accidental poisoning. This is consistent with both developed and developing countries that younger children are over- represented in acute accidental poisoning [ 3 , 5 , 11 ]. This is due to younger children being more inquisitive and exploratory in nature compounded by their newly acquired hand skills and mobility and increased the tendency to mouth objects [ 15 , 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…This differs from previously reported studies in the South Asian region from Sri Lanka, India, Pakistan in which kerosene was the most frequently ingested agent amongst a paediatric population [ 5 , 8 , 11 , 15 , 19 ]. This also differs from developed countries, whereby pharmaceuticals are the most common cause of paediatric poisoning hospital presentations [ 3 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, higher poisoning hospitalisations in remote areas may suggest more children are being poisoned, but also that children presenting to rural hospitals are more likely to be admitted4 16 for reasons including distance from facilities, limited specialist services and delayed diagnostic tests 23 32. Differences in poisoning agents by geographical region may also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the death rate from poisoning in children and adolescents under 20 years old is about 1.8/100,000 worldwide. So, one of the most common emergencies in childhood is toxic emergencies [1] [2] [3].…”
Section: Introductionmentioning
confidence: 99%